On the asymmetric evolution of the optical properties of a conjugated polymer during electrochemical p- and n-type doping. Issue 19 (28th April 2017) - Lanz, T.; Lindh, E. M.; Edman, L.
Abstract : The complex refractive index of a conjugated polymer is measured during electrochemical doping, and the response to p-type and n-type doping is highly asymmetric. Abstract : We report on the in situ measured evolution of the spectral complex refractive index of a prototypical conjugated polymer, a phenyl-substituted poly( para -phenylenevinylene) copolymer (Ph-PPV, "Super Yellow"), during electrochemical p- and n-type doping. We find that the real part of the refractive index is lowered in a significant and continuous fashion over essentially the entire visible range with doping, as exemplified by a drop in the peak value at ∼480 nm from 2.1 for pristine Ph-PPV to 1.8 at a p-type doping concentration of 0.2 dopants per repeat unit and an n-type doping concentration of 0.6 dopants per repeat unit. The imaginary part features a concomitant distinct bleaching of the high-energy π–π* transition and the emergence of a low-energy polaron band. Interestingly, we observe that the optical response of Ph-PPV to p-type and n-type doping is highly asymmetric, with the former resulting in much stronger changes and a distinct blue-shift of all optical transitions. We tentatively attribute this difference in response to larger effective size of the p-type polaron compared to the n-type polaron. We anticipate that the presented results should be of value for the rational design of emerging optical devices that utilize the doping capacity of conjugated polymers.